18F-FDG PET in Posterior Cortical Atrophy and Dementia with Lewy Bodies - Whitwell, Jennifer L; Graff-Radford, Jonathan; Singh, Tarun D; Drubach, Daniel A; Senjem, Matthew L; Spychalla, Anthony J; Tosakulwong, Nirubol; Lowe, Val J; Josephs, Keith A (The Journal of nuclear medicine (1978), 2017)
Posterior cortical atrophy (PCA) and dementia with Lewy bodies (DLB) have both been associated with occipital lobe hypometabolism on 18F-FDG PET, whereas relative sparing of posterior cingulate metabolism compared with precuneus/cuneus (i.e., cingulate island sign) is a feature of DLB. We aimed to determine whether patterns of hypometabolism or the cingulate island sign differed between PCA and DLB. Methods: Sixteen clinically diagnosed PCA and 13 probable DLB subjects underwent 18F-FDG PET. All PCA subjects showed β-amyloid deposition on PET scanning. Regional hypometabolism was assessed compared with a control cohort (n = 29) using voxel- and region-level analyses in statistical parametric mapping. A ratio of metabolism in the posterior cingulate to precuneus plus cuneus was calculated to assess the cingulate island sign. In addition, the 18F-FDG PET scans were visually assessed to determine whether the cingulate island sign was present in each subject. Results: PCA and DLB showed overlapping patterns of hypometabolism involving the lateral occipital lobe, lingual gyrus, cuneus, precuneus, posterior cingulate, inferior parietal lobe, supramarginal gyrus, striatum, and thalamus. However, DLB showed greater hypometabolism in the medial occipital lobe, orbitofrontal cortex, anterior temporal lobe, and caudate nucleus than PCA, and PCA showed more asymmetric patterns of hypometabolism than DLB. The cingulate island sign was present in both DLB and PCA, although it was more asymmetric in PCA. Conclusion: Regional hypometabolism overlaps to a large degree between PCA and DLB, although the degree of involvement of the frontal and anterior temporal lobes and the presence of asymmetry could be useful in differential diagnosis.Posterior cortical atrophy (PCA) and dementia with Lewy bodies (DLB) have both been associated with occipital lobe hypometabolism on 18F-FDG PET, whereas relative sparing of posterior cingulate metabolism compared with precuneus/cuneus (i.e., cingulate island sign) is a feature of DLB. We aimed to determine whether patterns of hypometabolism or the cingulate island sign differed between PCA and DLB. Methods: Sixteen clinically diagnosed PCA and 13 probable DLB subjects underwent 18F-FDG PET. All PCA subjects showed β-amyloid deposition on PET scanning. Regional hypometabolism was assessed compared with a control cohort (n = 29) using voxel- and region-level analyses in statistical parametric mapping. A ratio of metabolism in the posterior cingulate to precuneus plus cuneus was calculated to assess the cingulate island sign. In addition, the 18F-FDG PET scans were visually assessed to determine whether the cingulate island sign was present in each subject. Results: PCA and DLB showed overlapping patterns of hypometabolism involving the lateral occipital lobe, lingual gyrus, cuneus, precuneus, posterior cingulate, inferior parietal lobe, supramarginal gyrus, striatum, and thalamus. However, DLB showed greater hypometabolism in the medial occipital lobe, orbitofrontal cortex, anterior temporal lobe, and caudate nucleus than PCA, and PCA showed more asymmetric patterns of hypometabolism than DLB. The cingulate island sign was present in both DLB and PCA, although it was more asymmetric in PCA. Conclusion: Regional hypometabolism overlaps to a large degree between PCA and DLB, although the degree of involvement of the frontal and anterior temporal lobes and the presence of asymmetry could be useful in differential diagnosis.